Analisis Risiko Potensi Kegagalan Proses Penjernihan Air Limbah Industri Farmasi Dengan Pendekatan Metode AHP - Rimantho, Dino (Muhammadiyah University Press, 2019)
The pharmaceutical industry has the potential to produce waste water which is categorized as hazardous waste. The operational process of waste treatment has the potential to pose a risk of processing failure. The purpose of this article is to analyze the risks that occur in the pharmaceutical industry wastewater treatment process. This study uses the Analytichal Hierarchy Process (AHP) method. The number of experts used was three people. The results show that there are four main factors that have the potential to produce a risk of failure of wastewater treatment processes such as man, machinery, method, and material. The method factor is the highest risk factor which is around 0.609 with a consistency ratio of 0.08. In addition, the Sub-criteria that have the potential to experience the risk of process failure are the Standard Operational Procedure (SOP) which has not run optimally which is equal to 0.701. Furthermore, in assessing the level of risk obtained, the optimal SOP is run at 0.685. The implication of the application of the AHP method is that a more in-depth review is needed regarding the criteria and sub-criteria used to obtain more comprehensive results.